Chinese religion - Deborah Sommer (Oxford University Press, 1995)
For centuries, westerners have referred to China's numerous traditions of spiritual expression as "religious"--a word born of western thought that cannot completely characterize the passionate writing that fills the pages of this pathbreaking anthology...